Dorothy Richardson’s Correspondence during the Second World War and the Development of Feminine Consciousness in Pilgrimage - Ivana TRAJANOSKA (E-REA)
As an unjustifiably marginalized forerunner of English modernism, Dorothy Richardson left behind her, apart from her 13-volume novel Pilgrimage, a few short stories and poems, a considerable amount of non-fictional writings including essays and over two thousand letters. The majority of Richardson’s correspondence was first transcribed and edited by Gloria Fromm in Windows on Modernism. George H. Thomson systematized the total of Richardson’s known correspondence in his Dorothy Richardson: A Calendar of the Letters, enabling thorough research and unique insight in Richardson’s life. Furthermore, Richardson’s correspondence is of cultural value, even though Richardson, in her letters, accounts mainly for her daily life, financial constraints and constant moving to-and fro from Cornwall to London. However, her letters also, in a very subtle way, portray life in a world where socialism, communism and fascism were competing. Unlike some of her contemporaries, direct treatment of war is absent from both her novels and correspondence. Moreover, the letters written during the Second World War are particularly focused on domestic life in war time England. The present paper, through the analysis of Richardson’s correspondence during the Second World War and her unconventional way of dealing with current political and social events, aims to show Richardson’s unique approach to female experience and the development of feminine consciousness.